Keabsahan Letter C Sebagai Alat Bukti Kepemilikan Tanah - Ayu Lintang Priyan Andari; Miftahul Hasanah; Sumriyah Sumriyah (Jurnal Hukum dan Sosial Politik, 2023)
The problem of land is a problem that stems from the current needs of the community both for residential use, business or for community livelihoods such as to grow vegetables. In Indonesia, the regulation of land or agrarian has only existed since 1960, namely by bringing up the Basic Agrarian Law (UUPA). In the UUPA It has been stipulated that legal certainty regarding land can only be legally recognized by registering the land and obtaining a certificate of title to the land. Then there is a PP regarding land registration, namely PP No. 24 of 1997. Before the issuance of the UUPA in 1960, the community had a Letter C from the village as proof of ownership of land rights. Even today there are still people who still hold the Letter C as proof of ownership. This is what researchers will discuss about the validity of Letter C which is still used by some communities related to old evidence of ownership of land rights. In assessing the validity or not of a Letter C, it is necessary to understand what are the legal requirements of a decision